2000
DOI: 10.1007/s004420000342
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and direct effects of elevated CO 2 on seed provisioning, germination and seedling growth in Bromus erectus

Abstract: Elevated CO can affect plant fitness not only through its effects on seed production but also by altering the quality of seeds and therefore germination and seedling performance. We collected seeds from mother plants of Bromus erectus grown in field plots at ambient and elevated CO (m-CO, maternal CO) and germinated them in the greenhouse in a reciprocal design under ambient and elevated CO (o-CO, offspring CO). This design allowed us to examine both the direct effects of elevated CO on germination and seedlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 26 publications
3
52
1
Order By: Relevance
“…Our findings differ somewhat from germination studies of non-wetland species, which generally conclude that germination is little affected by elevated CO 2 (Garbutt et al, 1990;Huxman et al, 1998;Steinger et al, 2000;Poorter & Navas, 2003). In these terrestrial studies, a lack of germination density response to elevated CO 2 has been attributed partly to the fact that the CO 2 levels of terrestrial soils are higher than in the atmosphere (Bazzaz, 1979).…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings differ somewhat from germination studies of non-wetland species, which generally conclude that germination is little affected by elevated CO 2 (Garbutt et al, 1990;Huxman et al, 1998;Steinger et al, 2000;Poorter & Navas, 2003). In these terrestrial studies, a lack of germination density response to elevated CO 2 has been attributed partly to the fact that the CO 2 levels of terrestrial soils are higher than in the atmosphere (Bazzaz, 1979).…”
Section: Discussioncontrasting
confidence: 99%
“…Negative effects of CO 2 on seed quality were also reported for the related species Bromus erectus (Steinger et al 2000). However, these effects did not lead to transgenerational effects of CO 2 , possibly because reduced seed quality coincided with increased seed size under conditions of elevated CO 2 (Steinger et al 2000). In contrast, a study of spring wheat (Tritium aestivum L.) showed that this plant species did not respond to elevated CO 2 during the first generation.…”
Section: Introductionmentioning
confidence: 93%
“…This can be explained by a negative effect of elevated CO 2 on seed size and the nutritional quality of seeds, which results in reduced photosynthetic rates of the next-generation seedlings (Huxman et al 2001). Negative effects of CO 2 on seed quality were also reported for the related species Bromus erectus (Steinger et al 2000). However, these effects did not lead to transgenerational effects of CO 2 , possibly because reduced seed quality coincided with increased seed size under conditions of elevated CO 2 (Steinger et al 2000).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations